2023
DOI: 10.3389/fonc.2022.1072361
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Octreotide plus CVD chemotherapy for the treatment of multiple metastatic paragangliomas after double resection for functional bladder paraganglioma and urothelial papilloma

Abstract: BackgroundMetastatic pheochromocytomas and paragangliomas are rare neuroendocrine tumors with a poor prognosis. Bladder paraganglioma concomitant with urothelial papilloma is even rarer. However, the rate of tumor response to cyclophosphamide–vincristine–dacarbazine (CVD) chemotherapy and 5-year overall survival for patients with metastatic PPGLs remained lower. We described, for the first time, a case of a patient with multiple metastatic bladder PGL who received octreotide LAR combined with CVD chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Tumour recurrence, risk of malignancy and submucosal location can lend themselves to the difficulty of successful endoscopic resection. Conversely, cyclophosphamide/vincristine/dacarbazine chemotherapy has been seen to stabilise metastatic disease 31 32…”
Section: Discussionmentioning
confidence: 99%
“…Tumour recurrence, risk of malignancy and submucosal location can lend themselves to the difficulty of successful endoscopic resection. Conversely, cyclophosphamide/vincristine/dacarbazine chemotherapy has been seen to stabilise metastatic disease 31 32…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients can be completely cured after combination chemotherapy with cyclophosphamide, vincristine and dacarbazine, and stabilization of multiple metastatic paragangliomas of the bladder with octreotide in combination with cyclophosphamide, vincristine and dacarbazine chemotherapy has also been reported. [11,12] The temozolomide is also a classic drug for chemotherapy of paraganglioma. Therefore, it has been suggested that chemotherapy can be used as an adjuvant treatment for malignant paragangliomas.…”
Section: Discussionmentioning
confidence: 99%